PEMANFAATAN BIJI WANYI (Mangifera caesia Jack.) DALAM PEMBUATAN ETANOL SECARA HIDROLISIS ENZIMATIS DAN FERMENTASI MENGGUNAKAN Saccharomyces cerevisiae - Arissah, Nur; Sitorus, Saibun; Gunawan, Rahmat (JURNAL ATOMIK; Vol 5 No 2 (2020), 2020)
The utilization of wanyi seeds ( Mangifera caesia Jack.) in making ethanol by enzymatic hydrolysis and fermentation using Saccharomyces cerevisiae has been carried out. The method used is the hydrolysis of Î±-amylase and gluco-amylase enzymes, fermentation with time variation and yeast concentration as well as the addition of 0.5% urea nutrition and 0.06% NPK, distillation and gas chromatography. Ethanol content 98.508% at 6 days fermentation with yeast concentration 0.23%.